Estágio supervisionado IV: o uso do gênero textual glossário como recurso didático para o processo de letramento. - QUEIROZ, Keise Samanda Lima (2024)
This article aims to report the experiences lived during the Supervised Internship IV: Portuguese Language and its Literatures in High School, held at the Prof. Argentina Pereira State School of Integral High School, in Bragança, Pará. The study was conducted in a firstyear high school group, composed mainly of student from the countryside. The pedagogical proposal chosen was to work on the theme “manioc flour”, due to its social, cultural and economic relevance in the North region. Using the textual genre glossary, the objective for the lesson plan was to promote literacy and value the local culture, allowing students to become protagonists in the construction of knowledge. The theoretical foundation was based on some contributions of scholars, such as: Luiz Antônio Marcuschi (1996,2004), Kleiman (2005, 2007), Elias Rodrigues (2015), Pimenta and Lima (2008), among others. From the methodological point f view, a qualitative approach was adopted, based on the use of participants observation and field journal (Prodanov; Freitas, 2013). The results showed the active participation of the students, evidencing their pride in the transmission of knowledge and tradition and the feeling of belonging to the countryside. The importance of the internship in professional training is also highlighted, emphasizing the need for pedagogical practices adapted to the reality and social context of the students.